Fractal correlation properties of heart rate variability as a biomarker of endurance exercise fatigue in ultramarathon runners - Rogers B. Bruce; Mourot L. Laurent; Doucende G. Gregory; Gronwald T. Thomas (2021, 2021)
Title screen